WEBSITE UNIT PELAKSANA TEKNIS DINAS (UPTD) PUSKESMAS JEMBATAN KECIL KOTA BENGKULU MENGGUNAKAN ADOBE DREAMWEAVER CS3 - Yulianti, Liza; yono, Hari Aspri (Jurnal Media Infotama, 2011)
Science and technology evolve in line with the progress of activities undertaken to support humans. The computer is one of the results of human creation, combined with science to develop according to the needs of the user.This research aims to create a website Office Technical Implementation using Adobe Dreamweaver CS3,.The method used in this research is to use the method of system development. To get the required data the authors use data collection methods such as observation, interview techniques, and literature. Applications that are used in the manufacture of the Technical Unit Office website Jembatan Kecil Mini Hospital of Bengkulu is using Adobe Dreamweaver CS3, Programming Languages PHP, and MySQL as the database.These results indicate that the website needed to reduce the lack of information on the distance and time, so it does not have to come to get what is needed. Technical Unit Office website Jembatan Kecil Mini Hospital of Bengkulu should be able to run it online to be accessed anytime and anywhere through internet-connected computer.